Penerapan Model Pembelajaran Project Based Learning (PJBL) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Informatika Di SMA Negeri 5 Maros - Putri Aulia Salam; Nur Maya; Nasir Nasir; Dewi Hikmah Marisda; Rismawaty Parawansa (Institut Nalanda, 2024)
This research is classroom action research which aims to improve the learning outcomes of class X4 students at SMA Negeri 5 Maros in the informatics subject. This research was carried out in two cycles using a project- based learning model, Researchers carry out observations, interviews, tests and documentation. From the learning results in the first cycle, the number of students who reached the KKM was 17 students or 47.2% and those who did not reach the KKM were 19 people or 52.7% of the total number of students. In the second cycle the number of students who reached the KKM increased to 29 students or 80.5% and those who did not reach the KKM amounted to 7 students or 19.4% of the total students. Thus it can be concluded that the application of the project-based learning model can improve informatics learning outcomes for class X.4 SMA Negeri 5 Maros.